(untitled) (Plant Tissue Culture and Biotechnology, 2011)
MS with different concentrations and combinations of hormones were used for in vitro multiple shoot regeneration in two varieties of Brassica juncea, namely, BARI Sarisha-11 and BARI Sarisha-16 and one variety of Brassica campestris, Tori-7. The highest percentage of responsive explants towards the regeneration of shoots was obtained on MS with 2.0 mg/l BAP, 0.2 mg/l NAA and 0.5 mg/l Kn in case of BARI Sarisha-11 and BARI Sarisha-16. For Tori-7, 3.0 mg/l BAP and 0.2 mg/l NAA was best for obtaining maximum number of shoots per explant. Among three varieties, BARI Sarisha-11 showed best response in terms of shoot regeneration as well as number of shoot per explant. Days required for induction of shoots was also recorded to be lowest in BARI Sarisha-11. Best root induction in BARI Sarisha-11 and BARI Sarisha-16 was achieved on hormone free MS. After proper hardening the in vitro regenerated plantlets were successfully transplanted into soil. Interestingly some of the in vitro regenerated shoots produced in vitro flowers on regeneration media as well as hormone free MS. Key words: Plant regeneration, Brassica juncea, Brassica campestris D. O. I. 10.3329/ptcb.v21i2.10235 Plant Tissue Cult. & Biotech. 21(2): 127-134, 2011 (December)